(untitled) (Revista de História Regional, 2021)
This paper aims to discuss the aggregation that occurred between small producers in the locality of Jaguarão/RS, during the period 1802 - 1835. Through a survey based on the analysis of 67 post mortem inventories, it was found that 51% of these producers did not declare the ownership of the land on which they kept their production units. However, this fact did not characterize an impediment to the emergence of these small rural establishments. On the contrary, mechanisms that aimed at social reproduction of certain family niches were used in that space, among these was aggregation. We realized that this practice was recurrent among people of the same family, so that the act of aggregating is understood as a social relationship where family strategies obeyed the life and productive cycle of these subjects, thus also comprehending as a response to the needs of subsistence of new families that were in their early productive life. Keywords: Small rural producers; Aggregates; Family; Life cycle; Family Strategies.